TITIK FOKUS ILOKUSI ARTIKEL PEMENANG PERTAMA LOMBA PENULISAN OPINI TINGKAT SLTA SEKALIMANTAN SELATAN - Yayuk, Rissari (Jurnal KATA, 2018)
This study examines the focal point of illustration of the first winner of the contest for writing opinion of the senior high school level in South Kalimantan. This study aims to describe 1) the focus point of illustration of the title of the first winner of the contest writing opinion of the senior high school level in South Kalimantan? 2) the focal point of information information of the first winner of writing contest for high school level opinion in South Kalimantan; 3) the focal point of illocution of the moral message of the first winner of the high school opinion writing contest in South Kalimantan. The study was conducted in October 2016 at Balai Bahasa Balai. The method used is qualitative deskreptif. The technique used in this paper is the sampling purposive sampling. The sample used as data is the first winner of the contest for writing the opinion of the senior high school level in South Kalimantan, in South Kalimantan Language Hall, in 2016. This first winner is named Norhidayah, a student of SMAN 4 Banjarbaru, with the title of Language Role in Introducing Children of Nation. Data analysis is done by steps, data collection, data identification, classification, selection and interpretation. The results of data analysis are presented in ordinary words with technical terminology. Based on the results of the study of the focal point of the article, the first winner of the South Kalimantan high school opinion writing contest includes the focus point of the title illusion, the focus point of information illocution, and the focus point of the illustration of the moral mandate. The focus of the title illustration can be seen in the meaning of its ilokusinya, language, and suitability of the theme in the title. The focus point of the information illumination of the article can be seen in its meaning of ilokusinya, its language style, and the type of discourse. The focus point of the illustration of its moral mandate can be seen in the author's expectations contained in the title, the focus of the information, and on the final paragraph of the paperMasalah yang dibahasa mengenai titik fokus ilokusi  artikel pemenang pertama  lomba penulisan opini tingkat SLTA se-Kalimantan Selatan. Penelitian ini bertujuan mendeskripsikan 1) titik fokus ilokusi judul artikel pemenang pertama  lomba penulisan opini tingkat SLTA se-Kalimantan Selatan? 2) titik fokus ilokusi informasi artikel pemenang pertama  lomba penulisan opini tingkat SLTA se-Kalimantan Selatan; 3) titik fokus ilokusi amanat moral  artikel pemenang pertama  lomba penulisan opini tingkat SLTA se-Kalimantan Selatan. Penelitian ini dilaksanakan pada bulan Oktober 2016 di Balai Bahasa Kalimantan Selatan. Metode yang digunakan adalah deskreptif kualitatif. Teknik yang digunakan dalam tulisan ini adalah pengambilan sampel purposive sampling. Sampel yang dijadikan data adalah artikel pemenang pertama lomba penulisan opini tingkat SLTA se-Kalimantan Selatan, di Balai Bahasa Kalimantan Selatan, tahun 2016. Pemenang pertama ini bernama Norhidayah, siswa SMAN 4 Banjarbaru, dengan judul Peran Bahasa dalam Mencerdaskan Anak Bangsa. Analisis data dilakukan dengan  langkah-langkah, pengumpulan data, indentifikasi data, klasifikasi, seleksi dan  interpretasi. Hasil analisis data disajikan dengan kata-kata biasa dengan terminologi yang teknis sifatnya. Berdasarkan hasil kajian titik fokus ilokusi artikel pemenang pertama  lomba penulisan opini tingkat SLTA se-Kalimantan Selatan  meliputi titik fokus ilokusi judul, titik fokus ilokusi  informasi , dan  titik fokus ilokusi amanat moral.Titik fokus ilokusi judul dapat dilihat pada makna ilokusinya, gaya bahasanya, daya bahasa, dan kesesuaian tema pada judul. Titik fokus ilokusi informasi artikel dapat dilihat pada makna ilokusinya, gaya bahasanya, dan jenis wacananya.Titik fokus ilokusi amanat moralnya dapat dilihat pada harapan penulis yang terdapat pada judul, fokus informasi, dan pada paragrap akhir karya tulis